Autonomous luggage carrying robot - Ratnayake, Ratnayake Mudiyanselage Malika Nisal; Bohez, Erik L.J.; Manukid Parnichkun; Lin, Than (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Development and advancement of the global village concept have encouraged people to travel regularly. Senior citizens, mothers with infants and differently abled people have encountered much difficulty in managing their luggage in airports and train stations. The Luggage Carrying Robot project is an attempt to ease out the burden of carrying luggage while traveling. This project utilizes the ultrasonic positioning techniques to detect and follow the user of the system. It is also equipped with a wireless control unit and an obstacle avoiding system.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2015
Keywords: Autonomous robots